IDDF2019-ABS-0108 Hepatic decompensation risk is reduced, but not eliminated after direct-acting antivirals: the role of spleen stiffness measurement. (June 2019) - Marasco, Giovanni; Dajti, Elton; Ravaioli, Federico; Colecchia, Antonio; Letizia Bacchi Reggiani, Maria; Colli, Agostino; Alemanni, Luigina Vanessa; Tame, Maria Rosa; Andreone, Pietro; Brillanti, Stefano; Azzaroli, Francesco; Mazzella, Giuseppe; et al.
Abstract : Background: Little evidence is available on the risk of hepatic decompensation (HD), mainly those related to portal hypertension (PH), after direct-acting antivirals (DAAs) in patients with HCV-related advanced chronic liver disease (ACLD). Our aims were: a) to evaluate the incidence of HD after DAAs, as well as the effect of such treatments on HD development and b) to assess the role of liver (LSM) and spleen (SSM) stiffness measurement in HD prediction after sustained virologic response (SVR). Methods: We performed in our tertiary centre a cohort study in 146 ACLD patients treated with DAAs and with available LSM and SSM both before and 6 months after end-of-treatment (EOT). A historical cohort of 92 consecutively enrolled untreated cirrhotic patients with active HCV-infection was used as a control group. A propensity score stabilized inverse probability weighting approach was used to account for differences between groups. Time-dependent models for HD prediction after SVR were applied to account for changes in LSM and SSM after DAA therapy. Results: Median follow-up in the DAA cohort was 33.5 (22 – 38) months. The HD incidence in this cohort was 7.07 (4.56–10.96) per 100 person-years (PYs), significantly higher than in the active HCV cohort, 19.75 (13.81–28.25) per 100 PYs. DAA therapy was an independent protective factor for HD development (hazard ratio [HR], 0.177; 95%Interval-of-confidence [CI], 0.081–0.390) (figure 1A ), whereas previous HD (HR, 5.982; 95%CI 2.434–14.702) and higher SSM values (HR, 1.025; 95%CI 1.006–1.045) were associated with a higher risk of the event. SSM≥54 kPa was independently associated with HD despite SVR achievement (HR, 4.678; 95%IC 1.307–16.744) (figure 1B ). The time-dependent model including SSM values at baseline and at 6 months after EOT predicted post-SVR HD development better than the models including LSM and its changes after therapy. Conclusions: The risk of HD is markedly reduced after DAA therapy, but not abolished. SSM is confirmed as an accurate surrogate of portal hypertension, able to stratify for the risk of HD development after DAA therapy more accurately than LSM.